Myanmar The state, community and the environment - Skidmore, Monique; Wilson, Trevor (ANU Press, 2007)
Despite deteriorating economic and developmental conditions, worsening environmental problems, and troubles arising from the unresolved status of its ethnic minorities, Myanmar seems no closer to a political resolution. Myanmar's economy continues to stagnate, with severe implications for its people. Low levels of international assistance have exacerbated the situation.Myanmar-the state, community and the environment examines the missed opportunities by government and opposition groups to find a way out of the political impasse and improve the standard of living of the people of Myanmar.This collection provides insights into the country's economic development, in particular the vital rice-marketing sector and the attempts to expand existing industrial zones. It focuses, for the first time, on Myanmar's environmental governance with in-depth case studies, and on the increasing need for effective environmental protection and sustainability.